2018
DOI: 10.1504/ijmc.2018.10007780
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the critical factors for successful M-commerce adoption

Abstract: Prior studies on technology acceptance models (TAM) have been widely used to examine mobile commerce (M-commerce). These studies usually have applied the structural equation modelling; however, the method has intrinsic limitations in terms of effectiveness and validity. The purpose of this study is to find the critical success factors influencing consumer adoption decision on M-commerce by integrating TAM and decision-making trial and evaluation laboratory. In order to verify the proposed approach, the Taiwane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…SVQ was another important factor, from the IS success model approved, to have a significant influence on the BI to adopt m-commerce. Our results are in accordance of the findings of Moorthy et al (2017) and Hsu and Yeh (2018) who found that m-commerce adoption positively influenced by SVQ. Indeed, customers who perceive using m-commerce as a simple and fast way to find what they want to purchase, are more motivated to adopt mcommerce for different purposes (i.e.…”
Section: Mobile Commerce Adoptionsupporting
confidence: 93%
See 2 more Smart Citations
“…SVQ was another important factor, from the IS success model approved, to have a significant influence on the BI to adopt m-commerce. Our results are in accordance of the findings of Moorthy et al (2017) and Hsu and Yeh (2018) who found that m-commerce adoption positively influenced by SVQ. Indeed, customers who perceive using m-commerce as a simple and fast way to find what they want to purchase, are more motivated to adopt mcommerce for different purposes (i.e.…”
Section: Mobile Commerce Adoptionsupporting
confidence: 93%
“…PE plays an important role in mcommerce adoption (Khalifa and Ning Shen, 2008;Zhang et al, 2012). For instance, in Taiwanese banks (Hsu and Yeh, 2018), Malaysia (Hung and Chou, 2014) and China (Sun and Chi, 2017) PE has positively influenced BI towards adopting m-commerce services. (Ajzen, 1988) 1.…”
Section: Performance Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…An organization or individual business person can decide to take no action, and this can only apply when there are no cost benefits associated with the procedure (Hsu & Yeh, 2018). This is a dangerous move by an organization, and often taken up by small firms.…”
Section: Company Perspectivementioning
confidence: 99%
“…However, it has been observed that retailing is shifting from the multichannel approach to omnichannel approach because of the introduction of advanced online channels and new digital channels like mobile channels. Consequently, there is a growing number of research studies which investigate mobile commerce, mobile marketing, and social commerce [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%